Workplace diversity, organisational climate and intention to stay of employees at a government department in Cape Town - Khedama, N. G. (Vaal University of Technology, 2025)
This study examined the relationship between workplace diversity, organisational climate and intention to stay of employees at a government department in Cape Town, South Africa. The global changes showed the benefits of a diverse workforce in organisations both private and public. This occurrence was partially as a result of businesses becoming more global in order to capture international markets. Notwithstanding the importance of workforce diversity, scholars have attempted to answer why employees leave or intend to switch employment and organisations. Employee shortages at Government institutions triggered the interest in determining the influence of organisational factors on intention to stay of employees. It was evident that organisations needed to find ways to retain employees and more so, diversified staff. This study was descriptive and correlational in nature and followed a quantitative research approach. The target population comprised employees who have been employed for more than 12 months at all levels, consisting of general employees, supervisors, managers, officials and support staff within the department. A simple random sampling method was employed to identify the respondents fitting the predetermined sample criteria. A total number of 241 questionnaires were received and analysed. Relevant areas, research methods and data acquiring procedures were described. Moreover, a correlation analysis was conducted to establish the strength and direction of the relationship between the factors. In addition, regression analysis was performed to determine the relationships between the variables. Finally, SEM was performed to confirm the predictive relationship between workplace diversity, organisational climate and intention to stay. The study found that workplace diversity and organisational climate were the determinants of intention to stay. In addition, workplace diversity was found to have a significant relationship with organisational climate. Based on these findings, limitations were outlined together with the recommendations and conclusions.
MM (LRM) (Labour Relations Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Workplace diversity; Organisational climate; Intention to stay; Employees, government department; Dissertation, Academic -- South Africa.; Diversity in the workplace.